Effect of Job Engagement and Job Insecurity on Job Performance of Patra Hotel & Convention Employees in Semarang : Covid-19 (International Conference of Graduate School on Sustainability (ICGSS), 2021)
Employees are human resources who have an important role in maintaining customer satisfaction. The impact of covid-19 occurs in an uncertain work environment due to technological changes, economic fluctuations, layoffs that increase employees' perceptions of work anxiety (Karatepe et al., 2020). COVID-19 has spread in Indonesia for a long time, since early March 2020 the corona virus entered Indonesia and spread very quickly, causing hotels and restaurants to have an occupancy of around 30%. Foreigners entering Indonesia are restricted as well as domestic tourists to prevent the transmission of COVID-19, this directly threatens the sustainability of the organization and its performance. In this context, the job insecurity experienced by hotel employees may be significant in determining how the industry can recover and survive. This research was conducted with quantitative methods. The population in this study were employees who worked at the Patra Hotel in Semarang. The research sample size is determined by 95 employees. Collecting data using online questionnaires using google form and interviews. The conclusion obtained in this study is that job engagement has a significant effect on job performance and perceptions of job insecurity have no significant and direct effect on job performance during the covid-19 pandemic.